Implementación de un tratamiento alternativo para la remoción de fósforo y nitrógeno en aguas residuales mediante absorbentes a base de semillas y tallos de moringa oleífera LAM. (2018)
In this degree project arose as an alternative treatment for the removal of nitrate and phosphate from waste water by absorbing elaborated from seeds and stems of Moringa Oleifera Lam, being useful that this plant possesses coagulating characteristics in the water clarification of agreement to different investigations. To achieve it they were obtained from the seeds and Moringa's stems, six types of adsorbents; seed without calcined rind SSCC, seed without dry rind SSCS, seed with dry rind SCCS, seed with calcined rind SCCC, calcined stems TC and dry stems TS, in addition tests of pitchers were realized and one was employed at the experimental process with residual domestic and industrial water with high place contained of nutrients, being reached Removals of 88.71, 90.97 and 98.81 % respectively in both types of water, turning into effective results in comparison with the efficiency of current technologies used for the same end, being the above mentioned, the principal aim of this study. After the experimental analysis of the results, one resorted to the technologies of analysis of variance ANOVA, with the purpose of obtaining a statistical argument of the information, which stops as conclusion that the time and the types of adsorbents influence the removal of nutrients.